Hadith #2478 - Sunan Abi Dawud - Abdur Rahman bin Abi 'Auf al-Jershy عبد الرحمن بن أبي عوف الجرشي; Huraiz bin 'Uthman bin Jabir حريز بن عثمان بن جبر الرحبي; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Mu'awiya ibn Abu Sufyan (Sunan Abi Dawud)
Miqdan bin Shuraih reported on the authority of his father. I asked A’ishah about settling in the desert (to worship Allaah in loneliness). She said “The Apostle of Allaah(ﷺ) would go out (from Madina) to these torrential streams. Once he intended to go out to the desert (for worshipping Allaah). He sent me a She-Camel from the Camels of sadaqah that was not used as a mount. He said to me “A’ishah be lenient, for leniency makes a thing decorated and when it is removed from a thing it
Grade: Sahih

Hadith #3476 - Sunan Abi Dawud - Ali bin al-J'ad al-Jauhri علي بن الجعد بن عبيد الجوهري; Hiban bin Zayd al-Shr'by; Huraiz bin 'Uthman bin Jabir حريز بن عثمان بن جبر الرحبي; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
On the authority of her father: My father asked the Prophet (ﷺ) for permission (to kiss his body). (When he was given permission), lifting his shirt he approached his body, and began to kiss and stick to him. He then asked: Prophet of Allah, what is the thing withholding of which is not lawful ? He replied: Water. He asked: Prophet of Allah, what is the thing withholding of which is not lawful ? He replied: Salt. He again asked: Prophet of Allah, what is the thing withholding of which is not l
Grade: Da'if

Hadith #4602 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Abdur Rahman bin Abi 'Auf al-Jershy عبد الرحمن بن أبي عوف الجرشي; Huraiz bin 'Uthman bin Jabir حريز بن عثمان بن جبر الرحبي (Sunan Abi Dawud)
The camel of Safiyyah daughter of Huyayy was fatigued, and Zainab had a surplus mount. The Messenger of Allah (ﷺ) said to Zainab : Give her the camel. She said: Should I give to that Jewess? Thereupon the Messenger of Allah (ﷺ) became angry and kept away from her during Dhu al-Hijjah, Muharram, and a part of Safar.
Grade: Sahih